Project-Based Learning Approach for Teaching Life Cycle Assessment in an Industrial Pollution Control Engineering Master’s Program - Rio Aryapratama; Muhammad Mufti Azis (Universitas Muhammadiyah Purwokerto, 2026)
Addressing the complex challenges of climate change requires analytical tools that enables evaluation of the environmental performance of industrial activities. Life Cycle Assessment (LCA) has emerged as one such key tool, providing a science-based framework to quantify environmental impacts across product and process life cycles. In Indonesia, LCA has gained increasing attention through policy initiatives such as the Ministry of Environment’s PROPER program, which mandates LCA assessments for certain performance ratings. To address the growing demand for LCA applications, higher education must ensure that graduates possess adequate methodological understanding and practical skills to apply LCA effectively in real-world contexts. This study evaluates the effectiveness of teaching LCA through a project-based learning (PBL) framework in the Industrial Pollution Control Engineering Master’s Program at Universitas Gadjah Mada (UGM). Survey data from three student cohorts (2023–2025) were used to assess students’ perceived learning outcomes, learning experiences, challenges, and post-course application of LCA. The results show that students developed strong conceptual understanding and practical competence in LCA, with high satisfaction regarding theory–practice alignment and instructor feedback. However, several challenges were identified, particularly regarding the transition from simplified exercises to more complex, data-intensive case studies, especially related to software use and inventory development. Importantly, large number of students reported continued interest or intended use of LCA in their academic or professional activities after completing the course. Overall, the findings indicate that a project-based learning approach effectively supports the development of applied LCA competencies and promote sustained participants’ engagement with life cycle thinking.